2014
DOI: 10.1016/j.ajo.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Long Overall Survival After Dendritic Cell Vaccination in Metastatic Uveal Melanoma Patients

Abstract: Dendritic cell vaccination is feasible and safe in metastatic uveal melanoma. Dendritic cell-based immunotherapy is potent to enhance the host's antitumor immunity against uveal melanoma in approximately one third of patients. Compared with other prospective studies with similar inclusion criteria, dendritic cell vaccination may be associated with longer than average overall survival in patients with metastatic uveal melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 57 publications
0
37
0
Order By: Relevance
“…1) involved autologous DCs exposed to autologous tumor-derived RNA, 196 tumor-cell lysates, [197][198][199][200][201][202][203] autologous tumor stem cell lysates, 204 self-renewing and proliferating autologous tumor cells, 205 allogeneic cancer cell line lysates, [206][207][208] TAAs or TAA-derived peptides [209][210][211][212][213][214][215][216][217][218] or a combination thereof. 219 Most clinical studies based on the latter approach preferred melanoma-associated differentiation antigens including premelanosome protein (PMEL; also known as gp100), antigens belonging to the melanoma antigen gene (MAGE) family, tyrosinase (TYR) and Melan-A (MLANA; also known as MART1) (Fig.…”
Section: Completed Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) involved autologous DCs exposed to autologous tumor-derived RNA, 196 tumor-cell lysates, [197][198][199][200][201][202][203] autologous tumor stem cell lysates, 204 self-renewing and proliferating autologous tumor cells, 205 allogeneic cancer cell line lysates, [206][207][208] TAAs or TAA-derived peptides [209][210][211][212][213][214][215][216][217][218] or a combination thereof. 219 Most clinical studies based on the latter approach preferred melanoma-associated differentiation antigens including premelanosome protein (PMEL; also known as gp100), antigens belonging to the melanoma antigen gene (MAGE) family, tyrosinase (TYR) and Melan-A (MLANA; also known as MART1) (Fig.…”
Section: Completed Clinical Trialsmentioning
confidence: 99%
“…230 Regarding the distribution across different cancer types ( Fig. 1), patients harboring melanoma were most commonly enrolled in these trials, 186,196,198,205,213,221,223,227,[231][232][233][234] followed by patients with prostate cancer, 206,208,212,215 glioma or glioblastoma (GBM), 185,197,202,219 hepatocellular carcinoma, 204,211,220 non-small cell lung carcinoma (NSCLC), 207,214,230 renal cell carcinoma (RCC), 201,203 esophageal carcinoma, 216,226 and pancreatic ductal adenocarcinoma, 209,217 among others. Of note, only two trials included a wide range of advanced solid tumors refractory to previous treatments.…”
Section: Completed Clinical Trialsmentioning
confidence: 99%
“…Ten patients showed stable disease at the first evaluation point, 3 months after start of vaccination, but 7 patients subsequently progressed before the first maintenance cycle of vaccine was started at 6 months. Seven (50%) patients survived more than 2 years after start of DC vaccination for metastatic UM [68] . The efficacy of this therapeutic DC vaccine remains to be investigated in a large prospective study with a more uniform antigenloading method to DC.…”
Section: Vaccinementioning
confidence: 99%
“…Dendritic cell vaccines have been used to treat several different types of cancer, including melanoma and prostate cancer (31). DeVries observed that melanoma patients who had T-cell infiltrates within their tumor prior to treatment with the dendritic cell vaccine had better survival outcomes.…”
Section: An Ounce Of Preventionmentioning
confidence: 99%